Use of Fermented Ensilage Based Diet in Enhancing the Growth of Common Carp (Cyprinus carpio var communis) - D., Manikandavelu; N., Neethiselvan; G., Jagatheesan; K., Sundarsanam (Fishery Technology, 2025)
Three isoprotein feeds containing 25% protein, namely, rice bran and groundnut oil cake (control), rice bran and fish meal, rice bran, fish meal and fermented fish ensilage were used in the feeding experiments. After 45 days of feeding trial in water recirculatory system, growth was considerably higher in fishes fed with ensilage based diet than the control and diet based on fish meal.